2021
DOI: 10.1093/jme/tjab053
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance and Productivity of a Lutzomyia longipalpis (Diptera: Psychodidae) Colony from an Area Endemic for Visceral and Cutaneous Leishmaniasis in Northeastern Brazil

Abstract: Studies on experimental sand fly infection require the availability of colonies and laboratory conditions. In Brazil, Lutzomyia longipalpis (Diptera: Psychodidae) (Lutz and Neiva 1912) is responsible for the highest infection rates by Leishmania spp. and this species is one of the most suitable species for laboratory colonization. In this study, we describe a method for growing Lu. longipalpis in laboratory conditions (10 generations) from natural populations sampled from a region of high endemicity for viscer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…These results are much lower than other studies that analyzed this parameter. In 2021, Ribeiro da Silva et al [37] found an average fecundity of 33 in L. longipalpis;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are much lower than other studies that analyzed this parameter. In 2021, Ribeiro da Silva et al [37] found an average fecundity of 33 in L. longipalpis;…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, larval mortality is considered one of the main problems for the colonization of sandflies in the laboratory and, in particular, in the first stage, in which, due to their small size and low strength, individuals can be trapped in mycelia or in moisture condensation [33]. In contrast, Ribeiro Da Silva et al [37], obtained a low mortality in pupae of L. longipalpis, arguing that the reason may be due to the fact that, at this stage, they do not feed and prefer dry environments in which invasion by fungi and other microorganisms is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Ribeiro Da Silva et al . [ 39 ] also reported that average egg production of individualized females was lower in the established colony of Lu . longipalpis than that of females who remained in groups (31.4 and 35.7, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Ribeiro da Silva et al . [ 39 ] found an average fecundity of 33 in Lu . longipalpis ; Escovar et al .…”
Section: Discussionmentioning
confidence: 99%
“…Specimens of Lu. longipalpis were reared in the laboratory, free from Leishmania infection, as previously described 21 . Twelve hours before the experiments, the feeding of female sand flies was suspended to increase the probability of the insects feeding on the mice infected by L. (L.) amazonensis (IFLA/BR/1968/PH8 strain).…”
Section: Methodsmentioning
confidence: 99%